Pandangan Hukum Pidana terhadap Hubungan Sesama Jenis di Indonesia - Anak Agung Istri Adhi Pramesti; Diah Ratna Sari Hariyanto (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2024)
The aim of writing this journal is for readers to see more about the perspective of criminaI law in dealing with the specifics of same-sex relationships in Indonesia. The research was carried out using normative legal methods so that it is necessary to criminalize or expand criminal regulations for deviant acts committed by the LGBT community in reforming criminal law. The study results show that same-sex relationships are considered to violate norms in Indonesian society. Many people are uncomfortable with the presence of LGBT in their environment, which makes people question how the law in Indonesia handles cases of same-sex relationships. Meanwhile, same-sex relations carried out by LGBT people are not yet regulated as a criminal offense according to Indonesian criminal law, the regulation is still very limited because it only regulates same-sex sexual relations committed by adults with minors.